CHINA’S COVID – 19 RESPONSE STRATEGIES IN KUNMING YUNNAN PROVINCE - Fanxi Dai, (PEOPLE: International Journal of Social Sciences, 2026)
China, the country where the first cases of COVID-19 were detected and which was profoundly impacted by the global pandemic, has been a focal point for scrutiny and research regarding governmental performance and infection management. In the early stages of the epidemic, China swiftly implemented stringent lockdown and control measures, which proved effective in rapidly controlling the number of infections and maintaining them at a very low level for an extended period. However, following the official announcement on December 7, 2022, marking the end of the "Dynamic-Zero-COVID policy," China experienced a significant surge in infections. This outcome appears to have deviated from the Chinese government's initial plans, primarily due to the difficulty in balancing strict containment measures with economic stability. Consequently, the intensity of these policies was gradually relaxed until their complete cessation. The case of China demonstrates that the government's capacity to manage national crises is constrained by fragmented state power and increased autonomy among local administrative units. It is therefore inappropriate to view China through the lens of traditional West- philia assumptions. Instead, we must adopt a more open and contemporary perspective when analyzing the impact of COVID-19 in China. It is necessary to recognize that the Chinese government operates as a complex system characterized by decentralization, fragmentation and internationalization. Therefore, this paper aims to explore two questions through qualitative research: 1. How should we make sense of the Chinese government's prompt shift from a Dynamic Zero-COVID policy to an Opening-Up policy? 2. How did the local authority contribute to the decision-making of central government on the removal of Dynamic COVID–19 policy? I argue that the theory of securitization can serve as a valuable framework for understanding and explaining China's comprehensive policy response to the COVID-19 pandemic. However, given the dispersion of power and interests among various units, deviations in objectives and conflicts are inevitable. Consequently, the process of securitization does not conform to a simplistic or idealized model. Instead, “contestation” occurs throughout the process, and the roles of “actors” and “audiences” are fluid rather than fixed, undergoing constant transformation. Furthermore, the research perspective applied in this article has value for the study of issues in other authoritarian countries.